HPLC Analysis with Evaluation of Antioxidant and Antisenescence Activities of Parijoto (Medinilla speciosa Reinw. ex Bl.) Methanolic Extract in Vero Cells - Anif Nur Artanti; Sholichah Rohmani; Diyah Tri Utami; Nindita Clourisa Amaris Susanto; M. Fiqri Zulpadly; Annisa Diyan Meitasari; Ulfa Afrinurfadhilah Darojati; Meta Kartika Untari; Heru Sasongko; Dian Eka Ermawati; Feri Setyawan (Indonesian Journal of Cancer Chemoprevention, 2025)
Parijoto (Medinilla speciosa Reinw. ex Bl.) is a traditional medicinal plant rich in polyphenolic compounds that are associated with antioxidant and cytoprotective activities. The present study aims to investigate the phytochemical profile, antioxidant capacity, cytotoxicity, and anti-senescence effects of parijoto methanolic extract. The methanolic extract of parijoto (MEP) was subjected to qualitative thin-layer chromatography (TLC) for the detection of flavonoids, quantitative high-performance liquid chromatography (HPLC) for the determination of quercetin and naringin, and antioxidant activity assessment using the DPPH method. The mobile phase for quercetin analysis was water: acetonitrile (45:55), while for naringin, it was acetonitrile:water: formic acid (21:78.8:0.2). Cytotoxicity was evaluated in Vero cells using the MTT assay, while senescence in normal kidney cells was assessed by senescence-associated β-galactosidase (SA-β-gal) staining. Results showed that the extract contained quercetin (5.76±0.11 ppm). The extract exhibited strong antioxidant activity with an IC₅₀ value of 40.46 ppm. Cytotoxicity testing of MEP on Vero cells revealed low toxicity (529±0.77 μM) at physiologically relevant concentrations, supporting its safety for normal kidney cells. Moreover, in normal kidney cells, the extract conferred cytoprotective effects by reducing oxidative stress–induced damage and attenuating senescence-associated β-galactosidase. Collectively, these findings suggest that MEP exhibits potent antioxidant, cytoprotective, and anti-senescence activity in vitro, warranting further in vivo studies to validate its potential effects on kidney health and age-related cellular damage.